Do minimum wages really increase youth drinking and drunk driving? - Joseph J. Sabia; M. Melinda Pitts; Laura Argys (Federal Reserve Bank of Atlanta, 2014)
Adams, Blackburn, and Cotti (ABC) found that increases in minimum wages were positively related to drunk driving-related traffic fatalities for those ages 16 to 20. The hypothesized mechanism for this relationship - increased alcohol consumption caused by minimum wage - induced income gains - remains empirically unexplored. Using data from two national behavioral surveys and an identification strategy identical to ABC, we find little evidence that an increase in the minimum wage leads to increases in alcohol consumption or drunk driving among teenagers. These results suggest a much smaller set of plausible causal channels to explain ABC's findings.
Keywords: J38; K42; 330; minimum wage; teen drunk driving; alcohol consumption